An Efficient Incremental Query Recommendation based Query Ranking Model - B. Venkata Ramana Reddy (International Transactions on Electrical Engineering and Computer Science, 2022)
To retrieve the information from web, search area query estimation depending on the minor query logs is selected as an outstanding method. The log data will be developed very quickly. When new data models are developed the existing models should be updated. In this paper to keep the data up to date a new improved query ranking model is implemented. The new data is added to the existing model incrementally. The results shows the incremental query ranking model based techniques are better efficient than the existing query ranking model with better accuracy.